Performance analysis of a large-area luminescent solar concentrator module. (April 2015) - Aste, N.; Tagliabue, L.C.; Del Pero, C.; Testa, D.; Fusco, R.
Abstract: Today Luminescent Solar Concentrators (LSCs) represent a very promising solar technology, especially the semi-transparent ones, suitable for building integration. These components can likely represent an effective way to produce renewable energy while preserving the transparency of the building envelope, by using a wide amount of surfaces which at the moment are neglected, such as windows, skylights, shading devices, etc. This paper describes the first operating measurements carried out on a new LSC prototype, monitored at the Photovoltaic (PV) Test Facility of the Politecnico di Milano. The photoluminescent composition of the ENI dye used for the spectrum converter dispersed in the LSC includes an acene compound and a benzothiadiazole compound. The preliminary results show a better energy performance ratio for the LSC in comparison with standard PV modules, and are representative of the first phase of a research work aimed at industrializing an innovative building integrated component with a large dissemination potential. Highlights: We designed and realized a new LSC prototype able to be integrated in the building envelope. We carried out a monitoring campaign during summer. We compared the energy performance of LSC prototype with standard modules in clear sky and in partially cloudy conditions. We demonstrated the LSC wider exploitation of the solar cells' quantum efficiency, with a higher conversion rate.